Mass Transfer Kinetics during Osmotic Process of Sweetened White Radish - Nunak, Navaphattra; Mukprasert, Amornrat (Engineering and Applied Science Research, 2012)
The objective of this paper was to study the effect of ratios of samples to osmotic solution and pressureon mass transfer values during the osmotically sweentened white radish process at room temperature. Masstransfer during osmotic dehydration was modeled using Fickps second law of diffusion. From the experiment, itwas found that water loss and solid gain increased with increasing of ratio of samples to solution andpressure. However, an addition of solution and pressure also decreased the driving force of osmotic process.The effective diffusivity values in this research were found to be in the range of 5.75 x 10-8 m2/s to 2.57 x 10-7m2/s for water loss and 4.64 x 10-8m2/s to 1.12 x 10-7 m2/s for solid gain.